STUDENTS’ PERSPECTIVES ON THE IMPACT OF USING VIDEO CONFERENCES IN ONLINE LEARNING PROCESS - Kusumawardani, Liya; Hawa, Faiza; Nur’aini, Siti (Jurnal Ilmiah Spectral, 2022)
This research aims to describe the learning process while using video conferences and to find out the impact of using video conferences in online learning. This research involved the 7th-semester students of the English Department of the University of PGRI Semarang. The method used is qualitative descriptive by providing an open questionnaire and in-depth interviews to collect the data. The results of this study indicated that according to the students, the use of video conferences is very helpful for teaching and learning activities in online learning, and it is also more practical and safer to be used for learners during the pandemic. Then, the impact of using video conferences from the students’ perception can be identified from the positive and negative impacts. The positive impacts of using video conferences can be seen from point of view of time effectiveness, student communication, students’ participation during the teaching and learning activity, and student achievement. Meanwhile, the negative impacts of using video conferences can be seen in the lack of understanding of the materials and the high cost for students’ needs.